Antioxidant and immunomodulatory effect of chlorophyllin on induced aflatoxicosis in broilers - THAKUR, CHAMELI; KUMAR, B KALA; REDDY, A GOPALA; REDDY, A RAJASHEKAR; REDDY, Y N (The Indian Journal of Animal Sciences, 2011)
Chlorophyllin a known antioxidant was assessed against aflatoxin induced toxicity in broilers. Day-old male broiler chicks (60) were randomly divided into 4 groups (15). Group 1 (basal diet) served as healthy control, group 2 (aflatoxin @ 1 ppm) as toxic control, group 3 (chlorophyllin @ 500 ppm) as chlorophyllin control throughout the experiment of 6 week, and group 4 was fed aflatoxin @ 1 ppm of feed up to 4 weeks and thereafter treated with chlorophyllin @ 500 ppm of feed till the end of sixth week. Antioxidant action was assessed by glutathione, immunity status was evaluated by haemagglutination inhibition, aspartate aminotransferase (AST) and total protein served as hepatototxic biomarkers and lipid profile (total cholesterol, triglycerides, HDL and LDL) at the end of fourth and sixth week. Histopathological studies of bursa, liver and thymus were done to draw possible conclusions at the end of the experiment. Aflatoxin adversely affected the above parameters. Chlorophyllin was able to restore these parameters at par with healthy control group. Thus, chlorophyllin was found to be effective as an antioxidant in preventing and countering aflatoxin induced toxicity by scavenging free raicals and restoring the activity of antioxidant defense mechanism.